Cervical Dysplasia and High-Risk Human Papillomavirus Infections among HIV-Infected and HIV-Uninfected Adolescent Females in South Africa - David H. Adler; Melissa Wallace; Thola Bennie; Megan Mrubata; Beau Abar; Tracy L. Meiring; Anna-Lise Williamson; Linda-Gail Bekker (Hindawi Limited, 2014)
Background. HIV-infected adolescents may be at higher risk for high-grade cervical lesions than HIV-uninfected adolescents. The purpose of this study was to compare the prevalence of high-risk HPV (HR-HPV) infections and Pap smear abnormalities between these two groups. Methods. In this cross-sectional study, we compared the HPV DNA and Pap smear results between 35 HIV-infected and 50 HIV-uninfected adolescents in order to determine the prevalence of HR-HPV genotypes and cervical cytological abnormalities. Comparisons were made using Pearson χ2 and independent-samples t-tests analyses, and associations between demographic and behavioral characteristics and HPV infections were examined. Results. HIV-infected participants were more likely to be infected with any HPV (88.6% versus 48.0%; P<0.001) and with at least one HR-HPV (60.0% versus 24.0%; P=0.001), and to have multiple concurrent HPV infections (68.6% versus 22.0%; P<0.001). HPV 16 and 18 were relatively underrepresented among HR-HPV infections. Abnormal Pap test results were more common among HIV-infected participants (28.8% versus 12.0%; P=0.054). A history of smoking was associated with HR-HPV infection. Conclusions. HIV-infected adolescents have an increased risk of infection with HR-HPV and of Pap test abnormalities. The majority of HR-HPV infections among our participants would not be prevented by the currently available vaccinations against HPV.